Correlation between mount wilson classifications to solar flares using solar dynamics observatory (SDO) and hinode satellites / N.A.M. Norsham, Z.S. Hamidi and N.N.M. Shariff - Norsham, N.A.M.; Hamidi, Z.S.; Shariff, N.N.M. (Universiti Teknologi MARA, 2022)
Space weather disruption is known to be caused by solar flares and coronal mass ejections, which is the motivation for this study. The Mount Wilson classification, or magnetic classification, is used to study sunspots or active regions (AR). Three active regions were analysed in this study to examine their correlation with flare production. We use statistical and observational analysis to identify our objective. Data used was from 2014 to 2019 and the associated ARs are AR 11967, AR 12403, and AR 12192. Further analysis was carried out on each of them using the white light, magnetogram, and AIA 1700 filter from Solar Dynamics Observatory (SDO,) NOAA (National Oceanic and Atmospheric Administration), Hinode, and Space Weather Live. According to this study, solar flares are associated with high magnetic flux density and the number and size of sunspots. There have been rearrangements and changes in the topology and energy of the magnetic field that resulted in a flare.